Soil fertility and nutrient management in tuberose (Polyanthes tuberosa L.) through substitution of chemical fertilizer with comlizer - BORAH, NILAY; DEKA, J.; DEKA, N. C.; BARUA, I. C.; MAHANTA, P. ,; UDDIN, HALIM; GOSWAMI, KASTURI (Journal of Soil and Water Conservation, 2021)
An experiment was conducted in 2012 and 2013 at Assam Agricultural University to assess various weed and nutrient management practices on growth and yield of tuberose and soil fertility status. Recommended dose of fertilizer (RDF) was evaluated in comparison with mixture of vermicompost and different proportions, i.e. 75, 50 and 35% of RDF (Comlizer) under three weed management treatments, viz., black polythene mulch (BPM), application of herbicides oxadiargyl 150 g/ha or Metribuzin 500 g/ha followed by grubber at 60 and 90 days after planting (DAP) in factorial randomized block design with three replications. In the first year, BPM significantly reduced weed population compared to integrated weed management involving pre-emergence herbicide application and mechanical weeding. However, no significant variation was observed in weed density and dry weight otherwise, irrespective of the years. There was comparable dominance of grassy and broadleaved weeds up to 60 DAP, which shifted to the dominance of the latter as the crop growth progressed. The effect of nutrient management practices on weed growth was not significant. Neither crop growth nor flower yield or yield attributing characters was affected by weed management practices. Highest flower yield in terms of number of spikes per plant, or fresh weight (q/ha) was observed with RDF and was at par with comlizer applied as vermicompost 250 g + 75% RDF, or vermicompost 200 g + 50% RDF, or vermicompost 250 g + 50% RDF per square meter. Application of comlizer as vermicompost 250 g + 35% RDF per square meter significantly reduced number of spikes/plant and fresh flower yield (q/ha). The contents of available N and P in soil increased following their application under integrated weed management, while that under BPM was inconclusive. The soil properties and available nutrient contents after harvest of the crop were not affected by the treatments.